Predictive Model of Blood Pressure Control Behavior in Efforts to Prevent Complications Using the Health Belief Model (HBM) Approach Among Hypertensive Patients - I Nyoman Purnawan; Ni Made Kurniati (An Idea Health Journal, 2025)
Background: In Denpasar City, the prevalence of hypertension and its complications has increased from year to year. The occurrence of complications among hypertensive patients is largely due to poor blood pressure control behavior. To improve patients’ blood pressure control behavior, it is necessary to develop a predictive model that considers social support from healthcare providers, as well as patients’ perceptions and beliefs. Objectives: To develop a predictive model of blood pressure control behavior using the Health Belief Model (HBM) approach. Methods: This study consisted of two phases: a quantitative phase using a cross-sectional design and a quasi-experimental phase employing a nonequivalent (pretest and posttest) control group design. The study was conducted over a two-month period in Denpasar City. The study population included hypertensive patients who were actively registered in the primary healthcare center's medical records. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) and cross- tabulation. Results: Of the 192 respondents, 59.8% were found to have poor blood pressure control behavior. The SEM analysis showed a good model fit, with behavioral factors such as self-efficacy (coefficient = 0.370; p = 0.001), healthcare provider support (coefficient = 0.244; p = 0.004), and perceived susceptibility (coefficient = -0.084; p = 0.000) significantly influencing blood pressure control behavior. The predictive behavior model was successfully developed based on the findings of the previous research stages. The intervention using the predictive behavior model effectively improved blood pressure control behavior (PR = 5.6; p = 0.022). Conclusion: The predictive behavior model based on the Health Belief Model (HBM) was successfully developed and demonstrated the ability to enhance blood pressure control behavior. Therefore, its application should be expanded to prevent complications among hypertensive patients in Denpasar City.